Faktor Penyebab Perceraian dan Dampaknya Terhadap Psikis Anak - M. Harwansyah Putra Sinaga; Ahmad Yasri; Olga Rizky Nadila; Amanda Geopani; Saida Amini Thasfa (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
This study aims to find out how the factors cause Divorce, and How it influences the Child's Psychology. This research method is a descriptive research with a qualitative approach. The selection of research subjects used purposive sampling techniques. Data collection methods used interview, observation, and documentation techniques. The research subjects were 3 parents and 3 children at GG Gaperta. Checking the validity of the data using inductive triangulation techniques. From the results of this study, 1) it was concluded that the factors causing parental divorce in the subject of this study were family disputes, the existence of ideal women/men, financial problems and lack of communication, and bad habits of parents. 2 ) The impact of divorce on the social attitude of the newly accepted child on Jln. Gaperta, among others: a) Children feel less attention and affection from their parents. b ) Attempts to attract attention due to lack of attention . c) Children tend to be quiet and low self-esteem in the social environment.